Improving Teacher Competence Through Industrial Internship Programs: Multi-case Study at Islamic’s VHS 1 Blitar and Veteran’s VHS 1 Tulungagung - Sinta Dewi Novitasari; Yoto Yoto; Widiyanti Widiyanti (South Sulawesi Education Development (SSED), 2024)
Advances in technology go hand in hand with innovation in the industry, so teachers must prepare students to satisfy industry needs. Teacher apprenticeship is a program that must be implemented in order to improve teacher competence. The approach used in this study is a qualitative approach with a multicase study type. Research on Islamic Vocational School 1 Blitar City and Veterans Vocational School 1 Tulungagung. Based on the findings, the implementation of teacher apprenticeship cannot be separated from the collaboration that exists between SMK and industry. The cooperation includes planning, implementation, evaluation and certification. Teacher internships can be carried out because schools provide support to teachers and industry which always provide opportunities. Obstacles in the implementation of teacher internships exist in the implementation time which must adjust the teacher's teaching hours, so that the implementation time is limited or waiting for holidays.